Síntese, caracterização estrutural, espectroscópica e análise do potencial fotocatalítico do aluminato de cobalto e potencial catalítico na preparação do biodiesel - Moraes, Paula Glazielli Paulino [UNESP] (2014)
This work describes the synthesis and characterization of cobalt aluminate powder with spinel structure, evaluating the evolution of the microstructure, crystallographic parameters, chemical bonds, electronic properties and of colors presented by materials as a function of the calcination temperature of powders. The influence of decrease of Al+3 ions in the system properties was also investigated. It was analyzed the catalytic potential of the aluminates for the synthesis of biodiesel. Also, it was analyzed the photocatalytic potential of the CoAl2O4, as well as of the CoAl2O4 in the presence of activated carbon (CoAl2O4/CA) in the degradation of methylene blue dye. Powders of stoichiometric cobalt aluminate, CoAl2O4, and non-stoichiometric, CoAl1,875O4- and CoAl1,75O4-, were prepared by modified polyol method and calcined at different temperatures. The powders were characterized by thermal analysis (TG/DSC), scanning electron microscopy (SEM), X-ray diffraction, infrared and Raman spectroscopy and Diffuse Reflectance spectroscopy in the UV-Visible region. The results showed a strong influence of the temperature of calcination over the properties of the powders. The cobalt aluminate is formed in larger quantities at 1000 °C. On the other hand, the decreasing of the amount of Al+3 ions difficults the formation of this phase. Infrared and Raman spectra of the powders showed bands below 800 cm-1 related to the vibrations of Co–O and Al–O bonds. From Rietveld structural refinement was found a small degree of spinel inversion structure also confirmed by spectroscopic analyzes. The values of band gap energy derived using Kubelka-Munk equation and Tauc graphic method are between 1.5-1.9 eV. The infrared spectra of the products of the catalytic reaction for biodiesel production showed slight modifications compared to the spectrum of the oil used as reagent, which may be indicative of the formation of biodiesel. The greater efficiency ...